Navigating the Health System : Diabetes Care in Georgia - Balabanova, D. (2012)
Background Effective delivery of diabetes care requires integration across specialist teams delivering recognized interventions, a reliable pharmaceutical supply, and promoting self-management. Drawing on a framework incorporating physical, human, intellectual and social resources, the paper examines how these challenges are managed in diabetes care in Georgia. Methods The rapid appraisal study triangulated data from interviews with users, providers and key informants from various institutions in four regions of Georgia; data on clinical and social outcomes from diabetes; legislative and policy documents. Results Diabetes-related mortality in Georgia is among the worst in Europe and Central Asia, in a context of conflict, economic collapse and weak institutions. Essential inputs for diabetes care are in place (free insulin, training for primary care physicians, financed package of care), but constraints within the system hamper the delivery of accessible and affordable care. There are no evidence-based guidelines on diabetes management, formal support and quality assurance. The scope of work of primary care practitioners is limited and they rarely diagnose and manage diabetes, which instead takes place within the vertical system. Access to insulin is problematic in rural areas. Obtaining syringes, supplies and hypoglycemic drugs and self-monitoring equipment remains difficult everywhere. Prevention and effective management of complications is limited, increasing adverse outcomes. Diagnosis and treatment of diabetes complications involve hospital admission and unaffordable out-of-pocket payments. The complexity of pathways to key stages of care obstructs continuous care. There are poor linkages between primary and secondary care and ineffective patient follow-up or monitoring of outcomes. There is little effort to promote self-care, adherence to drug regimens and appropriate lifestyle, or to empower patients. Conclusions Improving diabetes outcomes will involve simplifying pathways to care and drugs, reassessing staff roles and insulin distribution systems. This would require better co-ordination of the inputs into the system and development of an integrated and patient-centred model.